Effect of NPC1L1 polymorphism on warfarin stable dose in Chinese patients under heart valve replacement surgery. (13th October 2021) - Ma, Siqing; Luo, Zhiying; Zhou, Xinmin; Zhou, Honghao; Chen, Ling; Zhang, Wei
Abstract: Warfarin is the most often anticoagulant choice for preventable thromboembolism. Notably, vitamin K plays a vital role in the process of warfarin's anticoagulant effect. Therefore, we presume NPC1L1, a key transporter of vitamin K (VK) intestinal absorption, may modulate the anticoagulant effect of warfarin. Studies have shown that NPC1L1 (‐762T>C, rs2073548) and p53 (P72R, rs1042522) variations are implicated in influencing NPC1L1 expression. This study aimed to assess the association between these two variants and warfarin stable dose (WSD). A two‐stage extreme phenotype design was used to explore the influence of these two variants (rs2073548, rs1042522) on WSD variance in 655 Chinese patients undergoing heart valve replacement surgery. NPC1L1 rs2073548, p53 rs1042522, VKORC1 rs9923231 and CYP2C9 *1/*3 polymorphisms were genotyped by polymerase chain reaction‐restriction fragment polymorphism (PCR‐RFLP) or Sanger sequencing, respectively. WSD was identified when target monitoring international normalized ratio (INR) value at 2.0‐3.0. In the discovery phase, NPC1L1 rs2073548 A allele carriers occupied a significantly higher rate in the low dose group ( P  = .019). However, in the validation group, warfarin dosage in patients with the rs2073548 AA, AG and GG genotypes were 2.91 ± 0.97 mg/day, 3.02 ± 1.00 mg/day and 3.00 ± 1.06 mg/day, respectively. Multiple linear regression analysis results suggested that CYP2C9*3 and VKORC1 rs9923231, but not NPC1L1 rs2073548, were independent predictors of WSD in Chinese heart valve replacement (HVR) surgical patients.